Dependent Militarization And Africa’s Security: Analysis Of Nigeria And United States Relations. - Tarabinah, Wilfred M.; Okolo, Philips O. (Archives of Business Research, 2015)
International politics are characterized by global military capitalism, a situation which inspires hegemons to determine the direction of the militarization programme of peripheral countries. In this study we examine the military pact between Nigeria and the United States of America. Using empirical indicators such as U.S trade and investment in Nigeria; U.S. military aid to Nigeria; incapacity of the Nigerian state to enforce international law; incapacity of the Nigerian government to mediate conflict between international actors and host communities. The study posits that Nigeria and United States government military treaty undermines the Nigeria’s government capacity to enforce the liability of U.S. Corporations for the violations of international law in Nigeria.